Migration, TB control and elimination: Whom to screen and treat - Rendon, A.; Centis, Rosella; Zellweger, Jean Pierre; Solovic, Ivan; Torres Duque, C.A.; Robalo Cordeiro, Carlos; De Queiroz Mello, F.C.; Manissero, D.; Sotgiu, Giovanni (Elsevier, 2018)
Tuberculosis (TB) in migrants represents an important clinical and public health threat, particularly in low TB incidence countries. The current review is aimed to assess issues related to screening and treatment of migrants with latent TB infection or TB disease. Keywords: TB migrants, TB elimination, TB control screening.